In-situ measurement of Ti-6Al-4V grain size distribution using laser-ultrasonic technique. (September 2018) - Dong, Feng; Wang, Xiaochen; Yang, Quan; Liu, Huaqiang; Xu, Dong; Sun, Youzhao; Zhang, Yanjie; Xue, Renjie; Krishnaswamy, Sridhar
Abstract: A laser-ultrasonic system was established combining an 8 ns width pulsed laser for ultrasound generation and a two-wave mixing (TWM) interferometer for detection. Several Ti-6Al-4V samples were heat treated variously to get different grain sizes. Longitudinal wave back wall echoes were used to calculate the frequency dependent attenuation of ultrasound after the signals were denoised using wavelet transform. A model was built to calculate the log-normal distribution of grain size based on the correlation between the frequency dependent attenuation and the volumetric grain size distribution derived from electron backscattering diffraction data (EBSD) using Schwartz–Saltykov method. Graphical abstract: Unlabelled Image